Campo, habitus, competências e práticas de ensino dos professores de Matemática de escolas brasileiras do ensino médio estadual com bons resultados no Enem - Souza, Fábia Maria de (2017)
The educational field is the vehicle responsible for the development of the secondary habitus and institutionalized cultural capital of individuals, promoting systematized and formal knowledge, fostering the resources of individuals in social mobility, with schools being responsible for the operationalization of the teaching process and the actions of the teacher, the figure of the agent responsible for enabling the development of students' skills and abilities, through systematized and formalized knowledge and through their teaching practices. However, all the areas of knowledge evaluated in the Enem (INEP, 2014a, 2015) presented very low results, with most averages below 600 points, with the worst rates concentrated in Mathematics: 473.5 in 2014 and 467, 9 in 2015. Situation motivated the search for successful teaching practices of Mathematics teachers, whose objective is to propose an effort to improve Mathematics teaching. Research began from the exploration of the field to find the reference schools and make the description of teaching practices within a qualitative approach, the procedures of data collection were i) the survey of secondary data to identify the reference schools, That is, schools that have the best means among their peers; Ii) the study of multicasos to better understand the teaching practices of teachers, as well as their secondary habitus and institutionalized cultural capital, besides the field in which they are inserted. At the end, it found the existence of agencies (schools) with different teaching models - full-time education, with an average of 8 to 10 hours of classes per day, with full-time teachers. Regular teaching, with average working hours of 4 to 5 hours of classes per day. As for the specialization of these teachers, there is a great disparity, since about 14% of the teachers of the full-time schools and 68% of the regular schools have only a graduation, while the other professionals have some type of specialization. The results show that the teaching practices are similar in the two working regimes, which basically use six teaching strategies: expository classes dialogues; reading and interpretation of mathematical questions; resolution of activities; laboratory experiments; process, systematic and continuous evaluations; and development of projects and participation in olympics that stimulate the competitiveness among students. At the end, it considers as the next challenge to find ways to bring these experiences to teachers, especially in the State of Pará, in order to include in the proposals of public policies.